A procoagulant chemically sulfated mannan. (20th January 2016) - Gracher, Ana Helena P.; Santana, Aline G.; Cipriani, Thales R.; Iacomini, Marcello
Highlights: Sulfation of a mannan from yeast extract, an easily and inexpensive source. Sulfated mannan was structurally characterized by GC–MS and NMR. Sulfated mannan had a procoagulant effect on blood coagulation models. Abstract: Disorders of hemostasis can produce innumerous problems. Polysaccharides have been studied both as anticoagulant and as procoagulant agents. A mannan with a main chain of α-(1 → 6)-linked-Man p units, branched at O-2 mainly by side-chains of 2-O-linked-α-Man p units was chemically sulfated, structurally characterized by NMR and GC–MS (methylation, desulfation and methylation with trideuterated iodomethane), and tested in vitro and in vivo on blood coagulation models. Chemical analyses indicate a high degree of substitution on the sulfated polysaccharide. This polymer acted as a procoagulant agent, increasing blood coagulation in normal and hemophilic plasma, activated platelet aggregation and also decreased ex vivo aPTT. Polymers such as the sulfated mannan could be a helpful source of hemostatic agents to prevent hemorrhagic states.